(3GdYGde hadSaJjs - (3GdYdGa, eTgOs; (3GdUHGZ, CMeOs ((3GdbGgQIs (3CbdGe YQHjI ddfTQ hGdJhRjYs, 2019)
(3gPG djS cJGHG aj JGQjN GdadSaI , Hd aj GdJadSa PGJg (B. (3jWQM gPG GdcJGH eY HOGjGJ GdbQf GdMGOj hGdYTQjf GJLGgGJ LOjOI ddJacjQ hGdJCed JJYdb HeHGMK GdEdgjGJ , hGdQDjI GdefWbjI ddYGde , hfXQjI Gdbje GdchfjI GdNeSI , hfXQjI GdhUa GdeJaQO heHMK GdMbjbI PGJg , hfXQjI GdUOb , hefGgL GdCOdIs
Keywords: (3GdefWbs; (3GdhLhO, Ydes